An Analysis of Students’ Problems in Speaking English During Covid-19 at The Eleventh Grade Accounting 1 of Vocational High School 1 Jambi City - Meiralda Meiralda; Efa Silfia; Ridho Praja Dinata (Universitas Batanghari Jambi, 2022)
This research focuses on analysis student problems in learning to speak English at Vocational High School number 1 Jambi City. This research used qualitative research design. The aims of this research was to find out what problems students faced in speaking English during the covid-19 pandemic and the solutions students made to overcome these problems. In this case, a direct analysis of the problems faced by students in learning to speak English in the classroom during the covid-19 pandemic. This research took six students of class XI Accounting 1 as research subjects. This research used interview sheets and interviewed students to collect data. Based on the results of the study, regarding the problems of students in learning to speak at Vocational High School number 1 Jambi City, there were several student problems during the pandemic, located in the sixth question about the difficulty of speaking English, namely, lack of confidence, embarrassed to speak English, online learning made students feel less confident. self-confident. learning time in class, so that the problems faced by students are lack of pronunciation, fear of making mistakes when speaking English, lack of motivation of students in speaking English, students get into trouble because it is based on problems experienced and experienced by themselves. that happens in everyday life. In learning to speak English, and based on interviews, there are solutions to the problem, such as, using more English, translating sentences on Google, by listening to English music.